The tyranny of merit what's become of the common good? - Sandel, Michael J. (New York Straus and Giroux, 2020)
A world-famous political philosopher, and the bestselling author of Justice, reveals the driving force behind the resurgence of populism: the tyranny of the meritocracy and the resentments it produces
Includes index
Keywords: Polarization (Social sciences)--United States